Orchid Exploration in the Forest of Saenam Village as Nuftah Plasma Conservation - Ni Putu Yuni Astriani Dewi; Maria Yustiningsih; Maria Paulin Saridewi (Jurnal Penelitian Pendidikan IPA, 2022)
This research was conducted with the aim of determining the types of orchid species in the Saenam Protected Forest, North Middle East Regency, East Nusa Tenggara Province. The Saenam Protected Forest has an area of Â±10 km2, has biodiversity, including orchids. One of the information regarding the orchid inventory in Timor Mainland, especially in the Saenam Protection Forest, North Middle East Regency has never been reported. It is necessary to carry out this exploratory research as a basic data of the existing biological resources in the location. The research was carried out in July-September 2021. Sampling was carried out by purposive sampling with sampling using a plot method measuring 10 x 40 m. The distance of each plot is 10 m with the total number of plots in this study is 10 plots. The results showed that the types of orchids found in the Saenam Protection Forest were 9 genera of orchids. All orchids found in this study belong to the type of epiphytic orchid. The dominant orchids in this research area are Pholidota globusa, Dendrobium smilliae var. alba, and Dendrobium smilliae.Â The types of host trees found in the orchids were Pine and Forest Water Guava